Nucleotide-Binding Domain Leucine-Rich Repeat Containing Proteins and Intestinal Microbiota: Pivotal Players in Colitis and Colitis-Associated Cancer Development - Prossomariti, Anna; Sokol, Harry; Ricciardiello, Luigi (Frontiers in Immunology, 2018)
The Nucleotide-binding domain leucine-rich repeat containing (NLR) proteins play a fundamental role in innate immunity and intestinal tissue repair. A dysbiotic intestinal microbiota, developed as a consequence of alterations in NLR proteins, has recently emerged as a crucial hit for the development of ulcerative colitis (UC) and Colitis-associated cancer (CAC). The concept of the existence of functional axes interconnecting bacteria with NLR proteins in a causal role in intestinal inflammation and CAC aroused a great interest for the potential development of preventive and therapeutic strategies against UC and CAC. However, the most recent scientific evidence, which highlights many confounding factors in studies based on microbiota characterization, underlines the need for an in-depth reconsideration of the data obtained until now. The purpose of this review is to discuss the recent findings concerning the cross-talk between the NLR signaling and the intestinal microbiota in UC and CAC development, and to highlight the open issues that should be explored and addressed in future studies.